2016
DOI: 10.1371/journal.pone.0151797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statins on the Progression of Coronary Calcification in Kidney Transplant Recipients

Abstract: BackgroundCoronary calcification (CAC) is highly prevalent in kidney transplant recipients (KTRs) and has been associated with cardiovascular morbidity and mortality. Some studies have shown a reduction in CAC progression with statin therapy in the general and chronic kidney disease (CKD) populations.Objectives and MethodsThe aim of the present study was to evaluate the effect of statins on CAC progression in incident kidney transplant recipients. Patients were randomly assigned to the statin (n = 61, 10 mg da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 54 publications
(58 reference statements)
2
20
0
Order By: Relevance
“…Of the 29 included studies (32 unique cohorts), most focused on haemodialysis patients [ 10 , 17–35 ] (20 studies, 1499 patients) or kidney transplant recipients [ 30 , 33 , 36–41 ] (8 studies, 649 patients), 2 of which investigated both haemodialysis patients and kidney transplant recipients [ 30 , 33 ]. Three studies (92 patients) investigated peritoneal dialysis patients [ 29 , 42 , 43 ], one of which also investigated haemodialysis patients [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 29 included studies (32 unique cohorts), most focused on haemodialysis patients [ 10 , 17–35 ] (20 studies, 1499 patients) or kidney transplant recipients [ 30 , 33 , 36–41 ] (8 studies, 649 patients), 2 of which investigated both haemodialysis patients and kidney transplant recipients [ 30 , 33 ]. Three studies (92 patients) investigated peritoneal dialysis patients [ 29 , 42 , 43 ], one of which also investigated haemodialysis patients [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study (38 patients) investigated nocturnal haemodialysis patients [ 44 ]. Six studies were randomized controlled trials [ 17 , 22 , 23 , 32 , 35 , 36 ] (five evaluating pharmacological interventions, one evaluating dialysate calcium), two studies were non-randomized controlled trials [ 27 , 34 ] (one of which incorporated a retrospective control group [ 34 ]) and one was a pilot study [ 25 ] (all three evaluating pharmacological interventions). The 20 other studies were observational cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…sd‐LDL has not yet been systematically measured in pediatric renal transplant recipients. This would be an important area to research as data describing the effect of statin therapy on renal transplant patients are conflicting: One study demonstrated that it can lower sd‐LDL, while another did not find it to have any positive effect on coronary calcifications in this cohort …”
Section: How Important Is Hyperlipidemia With Regard To the Long‐termmentioning
confidence: 94%
“…This is a post-hoc analysis of a randomized, controlled, and open-label study that evaluated the effects of statin use on coronary artery calcification in 100 incident KTX recipients [ 20 ].…”
Section: Methodsmentioning
confidence: 99%